Infiltration capacity of compacted lime treated black cotton soil as hydraulic barrier material - Alkali, A. N.; Shettima, I. M.; Kurna , B. B.; Okunade, N. Y. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Studies have shown the effect of hydraulic barriers in the reduction in movement of leachates, that have the potential of contaminating groundwater. Laboratory tests were conducted on black cotton soil treated with up to 5% lime by dry weight to assess its suitability in waste containment facilities. The test samples were subjected to particle size distribution analysis, consistency limit tests, compaction and hydraulic conductivity. The compaction energy of British Standard Light (BSL) was employed. The study showed decrease in liquid limit from 65.20% to 56.30% and plasticity index from 41.50% to 28.58% while plastic limit increased from 23.70% to 27.72% with the increase lime content.  Maximum Dry Density (MDD) increases with increased in lime from 1.78  to 1.88 g/cm3 whereas the Optimum Moisture Content (OMC) decreased from 19.79% to 15.39%. Hydraulic conductivity of black cotton soil treated with percentage of lime content 0%, 1%, 3% and 5% of the soil weight examined for a period of 28days. The hydraulic conductivity value of natural soil was 1.65E-08 and decreased to 3.71 E-09 m/s at 5% lime content. Therefore, it is clear that hydraulic conductivity decreases with percentage increase in lime content. It is recommended that volumetric shrinkage, free swell and unconfined compressive strength should be carried out.